2016
DOI: 10.1111/aos.13326
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of scleral buckling using chandelier endoillumination

Abstract: There was no complication found due to the chandelier insertion in early postoperative period. Chandelier endoillumination is a feasible method for retinal visualization under surgical microscope during scleral buckling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 19 publications
2
33
0
Order By: Relevance
“…Furthermore, the only failed case of the control group was caused by an omitted hole. The better visualization of endo-illumination and noncontact wide-angle viewing system could reduce recurrence rate by sealing all retinal holes, even those that were not identified preoperatively, and make SB an option for the cases with small pupils or opacity of refractive media [10]. (2) The improved procedure had a shorter mean operation duration than conventional surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the only failed case of the control group was caused by an omitted hole. The better visualization of endo-illumination and noncontact wide-angle viewing system could reduce recurrence rate by sealing all retinal holes, even those that were not identified preoperatively, and make SB an option for the cases with small pupils or opacity of refractive media [10]. (2) The improved procedure had a shorter mean operation duration than conventional surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Despite zero occurrences in our study, the complications reported in previous literature should be considered, such as vitreous herniation from sclerotomy sites, vitreoretinal traction [6], endophthalmitis [15], iatrogenic retinal tears, or lens damage [5]. To reduce the complications, some points should be emphasized: (1) avoid inserting the illuminator probe into vitreous repeatedly, (2) avoid moving the probe rapidly and over-inserting, (3) do not stir vitreous, (4) examine the closure of sclerotomy site in case of vitreous herniation from sclerotomy sites and secondary vitreoretinal traction, (5) chandelier endo-illuminators might be another choice for limited insertion depth and less possible stir [10, 16].…”
Section: Discussionmentioning
confidence: 99%
“…Our study confirmed the advantages of the use of endoillumination and noncontact wide-angle viewing system which had been reported previously: (1)upright images of the fundus and better visualization for retinal details, (2)reducing the recurrence rate by sealing all retinal holes even those that were not identified preoperatively, (3)making scleral buckling an option for the cases with small pupils or opacity of refractive media, (4)shortened operation time, (5)enabling to obtain video record for further training and review, and finally, (6)eliminating surgeons' stress caused by bending neck and waist over and over again when using an indirect ophthalmoscope. Chandelier endoilluminators were also reported to be used combined with noncontact wide-angle viewing system [10]. But we believe that fiber illuminator might be a better choice because it could be aimed directly to the affected part to obtain a clearer sight view and Chandelier is more expensive and not so widely used as a routine surgical equipment.…”
Section: Discussionmentioning
confidence: 99%
“…Nam et al [11] reported a similar method soon. Hu et al [12] used 25-G endoillumination and a contact lens microscope in 2017. Caporossi et al [13] presented results of scleral buckling with a cannula-based 27-G chandelier endoilluminator in 2017.…”
Section: Introductionmentioning
confidence: 99%